Design of an Analog Spectrum Analyzer for Probing Experiments. - Zoughi,R; Moore,R K; Onstott,R G (1984)
A spectrum analyzer is required for analyzing the signal received by an FM-CW radar. For probing the ground and sea ice with an FM radar, logistics and economics considerations limit the kind of spectrum analyzer used. These limitations suggest the need for a simple, yet adequate and portable, spectrum analyzer. Hence, a spectrum analyzer was specified, designed and developed to serve these purposes. This report briefly introduces the kind of radar used for probing experiments and extensively describes the design and performance of this special-purpose spectrum analyzer.